Physiological demands of competitive surfing - Farley, O. R. L.; Harris, N. K.; Kilding, A. E. (The Journal of Strength and Conditioning Research, 2012)
This study was a performance analysis of surfing athletes during competitive surfing events in an attempt to inform the development of surfing-specific conditioning. Twelve nationally ranked surfers were fitted with heart rate (HR) monitors and global positioning system (GPS) units and videoed during the heats of 2 sanctioned competitions. Means and SDs represented the centrality and spread of analyzed data. From the 32 videos analyzed, the greatest amount of time spent during surfing was paddling (54 ± 6.3% of the total time) (% TT). The remaining stationary represented 28 ± 6.9% TT, wave riding, and paddling for a wave represented only 8 ± 2% TT and 4 ± 1.5% TT, respectively. Surfers spent 61 ± 7% of the total paddling bouts and 64 ± 6.8% of total stationary bouts between 1 and 10 seconds. The average speed recorded via the GPS for all the subjects was 3.7 ± 0.6 km/h, with an average maximum speed of 33.4 ± 6.5 km/h (45 km/h was the highest speed recorded). The average distance covered was 1,605 ± 313 m. The mean HR during the surf competitions was 139 ± 11 b/min (64% HRmax), with a (mean) peak of 190 ± 12 b/min (87% HRmax). Sixty percent TT was spent between 56 and 74% of the age-predicted HR maximum (HRmax), 19% TT >46% HRmax, and approximately 3% TT >83% HRmax. Competitive surfing therefore involves intermittent high-intensity bouts of all out paddling intercalated with relatively short recovery periods and repeated bouts of low-intensity paddling, incorporating intermittent breath holding. Surfing-specific conditioning sessions should attempt to replicate such a profile.